Improving the transition between paediatric and adult healthcare: a systematic review. Issue 6 (8th March 2011) - Crowley, R; Wolfe, I; Lock, K; McKee, M
Abstract : Introduction: The transition between paediatric and adult care for young people with chronic illness or disability is often poorly managed, with adverse consequences for health. Although many agree that adolescent services need to be improved, there is little empirical data on which policies can be based. Objectives: To systematically review the evidence of effectiveness of transitional care programmes in young people aged 11–25 with chronic illness (physical or mental) or disability, and identify their successful components. Design: A systematic literature review in July 2010 of studies which consistently evaluated health outcomes following transition programmes, either by comparison with a control group or by measurement pre-intervention and post-intervention. Results: 10 studies met the inclusion criteria, six of which showed statistically significant improvements in outcomes. Descriptive analysis identified three broad categories of intervention, directed at: the patient (educational programmes, skills training); staffing (named transition co-ordinators, joint clinics run by paediatric and adult physicians); and service delivery (separate young adult clinics, out of hours phone support, enhanced follow-up). The conditions involved varied (eg, cystic fibrosis, diabetes mellitus), and outcome measures varied accordingly. All six interventions that resulted in significant improvements were in studies of patients with diabetes mellitus, with glycosylated haemoglobin level, acute and chronic complications, and rates of follow-up and screening used as outcome measures. Conclusions: The most commonly used strategies in successful programmes were patient education and specific transition clinics (either jointly staffed by paediatric and adult physicians or dedicated young adult clinics within adult services). It is not clear how generalisable these successful studies in diabetes mellitus will be to other conditions.